Inclusive and Accessible Transportation for All: Strategies for Integrating Equity in Transportation Research - Laquanda Leaven Johnson; Oghenetejiri Ebakivie; Jerry Everett; Szaviea Wynn (Logistics, 2025)
Background: Transportation equity has emerged as a critical area of focus in recent studies. Integrating equity into transportation research is increasingly recognized as essential for developing fair, inclusive, and sustainable transportation systems. The significance of this integration lies in its potential to reduce social and spatial disparities, support economic growth, promote social cohesion, and advance public health. Methods: This literature review synthesizes recent research on the incorporation of equity into transportation studies within transportation planning and frameworks. It examines how equity is conceptualized, measured, and operationalized, focusing on both horizontal equity (the equal treatment of similar groups) and vertical equity (prioritizing disadvantaged populations). This study evaluates various methodologies and tools, such as accessibility indices, affordability metrics, and community engagement approaches, which are used to assess and promote equity in transportation systems. Results: The findings from this review highlight the importance of both horizontal and vertical equity in transportation planning and policy and foundational tools for assessing equity. Conclusions: Integrating equity into transportation research is vital for creating systems that are equitable, inclusive, and responsive to the needs of all communities. Addressing current challenges requires clearer and more consistent frameworks, improved data collection, and more inclusive, community-driven decision-making processes.